Nanotexturing of Conjugated Polymers via One-Step Maskless Oxygen Plasma Etching for Enhanced Tunable Wettability - Jiang, Youhua; Xu, Jian; Lee, Junghoon; Du, Ke; Yang, Eui-Hyeok; Moon, Myoung-Woon; Choi, Chang-Hwan (AMER CHEMICAL SOC, 2017)
A one-step maskless oxygen plasma etching process is investigated to nanopattern conjugated polymer dodecylbenzenesulfonate doped polypyrrole (PPy(DBS)) and to examine the effects of nanostructures on the inherent tunable wettability of the surface and the droplet mobility. Etching characteristics such as the geometry and dimensions of the nanostructures are systematically examined for the etching power and duration. The mechanism of self-formation of vertically aligned dense-array pillared nanostructures in the one-step maskless oxygen plasma etching process is also investigated. Results show that lateral dimensions such as the periodicity and diameter of the pillared nanostructures are insensitive to the etching power and duration, whereas the length and aspect ratio of the nanostructures increase with them. X-ray photoelectron spectroscopy analysis and thermal treatment of the polymer reveal that the codeposition of impurities on the surface resulting from the holding substrate is the primary reason for the self-formation of nanostructures during the oxygen plasma etching, whereas the local crystallinity subject to thermal treatment has a minor effect on the lateral dimensions. Retaining the tunable wettability (oleophobicity) for organic droplets during the electrochemical redox (i.e., reduction and oxidization) process, the nanotextured PPy(DBS) surface shows significant enhancement of droplet mobility compared to that of the flat PPy(DBS) surface with no nanotexture by making the surface superoleophobic (i.e., in a Cassie-Baxter wetting state). Such enhancement of the tunable oleophobicity and droplet mobility of the conjugated polymer will be of great significance in many applications such as microfluidics, lab-on-a-chip devices, and water/oil treatment.
Keywords: NANOWIRE ARRAYS; SURFACES; FABRICATION; DROPLET; CELLS